2016
DOI: 10.1001/jamaneurol.2015.4441
|View full text |Cite
|
Sign up to set email alerts
|

Stent Retrievers for the Treatment of Acute Ischemic Stroke

Abstract: IMPORTANCE Stent retrievers are a promising alternative for the treatment of acute ischemic stroke (AIS). Several recently completed clinical trials have examined the use of stent retrievers with intravenous recombinant tissue plasminogen activator (rtPA) compared with rtPA alone. OBJECTIVE To conduct a systematic review and meta-analysis of randomized clinical trials to quantify the benefits and risks of using stent retrievers in addition to rtPA for the treatment of AIS. DATA SOURCES The MEDLINE, EMBASE, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 21 publications
0
12
0
3
Order By: Relevance
“…Without measures for early detection, dysphagia may be less salient symptomatically than dysarthria and aphasia, thereby compromising timely medical interventions such as alternatives to oral medication [12] and increasing the risk of aspiration pneumonia [13]. Also, given the potential risks of thrombolytic or endovascular therapy for patients with acute ischemic stroke [14], it is important to be able to predict major post-stroke impairments based on initial imaging and clinical and demographic factors. Knowing the key factors associated with the presence of 1 or multiple debilitating impairments may facilitate decision-making for medical interventions where potential benefits outweigh risks.…”
Section: Introductionmentioning
confidence: 99%
“…Without measures for early detection, dysphagia may be less salient symptomatically than dysarthria and aphasia, thereby compromising timely medical interventions such as alternatives to oral medication [12] and increasing the risk of aspiration pneumonia [13]. Also, given the potential risks of thrombolytic or endovascular therapy for patients with acute ischemic stroke [14], it is important to be able to predict major post-stroke impairments based on initial imaging and clinical and demographic factors. Knowing the key factors associated with the presence of 1 or multiple debilitating impairments may facilitate decision-making for medical interventions where potential benefits outweigh risks.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the stentriever is the most commonly preferred device in approximately 90% of hospitals in Korea [8]. Stentriever use had some advantages such as easy handling, faster and complete reperfusion, temporal opening, and lesser bleeding complications [28,29]. There were increasing trends in successful recanalization (up to 87% in 2017) and rapid recanalization (mean intervals from door to final recanalization from 240.1 min in 2014 to 173 min in 2017) and decreasing trends in symptomatic intracranial hemorrhage, which might be related with growing use of stentriever over time in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of acute ischemic stroke treatment showed that patients randomized to stent retriever therapy with IV-rtPA had significantly improved rates of functional independence at 90 days compared with those randomized to IV-rtPA alone [ 6 ]. Additionally, the introduction of ADAPT dramatically improved the efficacy of aspiration thrombectomy, as it utilizes a flexible and atraumatic large-bore aspiration catheter that can access the intracranial vasculature and provide a large cross-sectional area for thrombus aspiration without having to completely traverse the occlusion [ 4 ].…”
Section: Discussionmentioning
confidence: 99%